Peranan Identifikasi Tes Dna Sebagai Alat Bukti Terhadap Sistem Perkara Pidana - tri susilowati (Justicia Journal, 2015)
Law is a written rule as a means to achieve the goal, which is to create an atmosphere of secure,peaceful, orderly, and prosperous. By because the law must involve along with the development ofsociety, Science and technology the changes in people’s live, affects all elements relating to the law,including the creation of rules of law, application of the law, and law enforcement, etc.One specific thing is the increasing incident of criminal matters, good quality, quantity, or modusoperandi. It thus should be able to function protective, must be balanced by the quality andresponsibility of the State as protector and public servant.Efforts to control and eradicate criminal incident, the State is obliged to carry out preventive andrepressive action. Both of the efforts must be implemented in a balanced way, in order to create, orderwith in the community. One effort that is emphasized is the repressive efforts, these efforts taken sothat the legal function as protectors of the people of the event that was about to rape her can beenforced.In the effort repressive, such as is done by applying the proof of the events Criminal Case, which isbased on the existing rules of positive law, in order to ensure the dignity and human dignity, theprotection of Human Rights, in particular to the perpetrators of criminal events, Related to the evidence,the law of criminal procedure adheres to the system of proof under the law is negative (negativewettelijk bewijs theories). Therefore, the guilt of the accused before the court is determined by thejudge’s convictionThe provision relating to evidence and legal evidence, in the process of proving a criminal casebased on the Code of Criminal Procedure, and other legislations. Linkage general rules with specific rulesmentioned above, as a consequence of the development of criminal law (criminalization).Along with the development of science and technology today, cause a shift of Science andTechn0ology, in an effort to identification of the victim and shifted to the Dactiloskopi Sciences toMedical Science B-DNA structure.The use of the science related to the experts who testified based on his expertise has value thestrength of evidence is a loose, non-binding and determine, judges can use when deemed necessaryaccording to the provisions of the Act. In practice, associated with things that are special, to clarify aparticular issue, the judge asked for assistance to the experts, who have special expertise in the field, inorder to understand the problems of technical and specific nature that are not controlled by the judge.When the judge faces the problems related to the absence of the identity of the victim, the judgecan use DNA testing of evidence. DNA tests, presence in court is required to assist judge inunderstanding the things that are technical and scientific correlated as evidence from expertstestimonies, letters, and instructions by the judge in order to strengthen his faith in order to find thematerial truth.Should legislative policy for creation of the Book of the Law of Criminal Procedure in the future,defined the formulation of clauses that regulate expressly qualified an expert and legal evidence, alongwith the development of science and technology, so as to overcome the constraints in criminalproceedings.Law enforcement should not only emphasize the rule of law, but shifted in the benefit of law, inline with the objective of criminal law to seek the material truth.